Serum neprilysin and the risk of death in patients with out-of-hospital cardiac arrest of non-traumatic origin - Zelniker, Thomas; Spaich, Sebastian; Stiepak, Jan; Steger, Florian; Katus, Hugo; Preusch, Michael (European heart journal - acute cardiovascular care, 2020)
Background: Early risk stratification remains an unmet clinical need in patients with in out-of-hospital cardiac arrest. We hypothesised that soluble neprilysin...
Gesehen am 20.07.2021